Analysis of the Gender Equality Application in Japanese and Indonesian Elementary School Education through Class Pickets - Tania Mulyahati; Linna Meilia Rasiban (Universitas Pendidikan Indonesia (UPI), 2021)
In the practice of implementing gender equality, education is one of the receptacles for students to comprehend the implementation of gender equality starting from a very early age. However, many hindrances happened upon the implementation of gender equality on students, especially on elementary school students. The purpose of this research is as stimulation to implement the social reality which became an issue to role holders in implementing character building-related gender equality by observing Japan’s implementation of gender education which can be a reference to look at. The research covering this topic has been done by many. One of them almost publishes a similar topic which was conducted in 2012 which discussed Gender Equality on Education at PPL PGSD-partnership Elementary School. Therefore, the writers try to research this by adding new formula by comparing discoveries in Indonesian and Japanese Elementary School. This research is a combination of descriptive-contrastive methods, historical research, data collecting by interviews on elementary school students, and supported by a few journals which discuss Japanese character building. The results of the research show that Indonesia does not fully enforce gender equality in the education system. This is proven from the daily classroom cleaning schedule which is inversely proportional to Japan’s character building that enforces gender equality, starting from the act of classroom cleaning modelled after the tokkatsu model or educational model. Hopefully, the upcoming researches which study these issues can be a literature study of social symptoms which can meet the solution so this issue can be resolved.